Women Seed Entrepreneurship Study: Key Findings from Results-Based Management Indicators - Kapur, Aman; Nayak, Prakash Kumar; Sahana, V. P.; Shivhare, Richa; Khan, Afreen; Puskur, Ranjitha (CGIAR System Organization, 2024)
This report presents the status of the Indicators outlined in the Results-Based Management (RBM) framework developed for the Seed-Entrepreneurship Study. The framework, led by the International Rice Research Institute (IRRI) in partnership with 3 partner organizations (POs) - the Access Livelihoods Foundation (ALF), the Centre for Sustainable Agriculture (CSA), and Pragati Koraput, focuses on developing decentralized seed systems and the empowerment of women seed producers (WSPs) through Farmer Producer Companies (FPCs) in Andhra Pradesh, Telangana, and Odisha. The RBM framework was established following the co-creation of a Theory of Change (ToC).